Vaccine Potential of a Recombinant Bivalent Fusion Protein LcrV-HSP70 Against Plague and Yersiniosis - Gupta, Ankit; Narayan, Bineet; Kumar, Subodh; Verma, Shailendra Kumar (Frontiers in Immunology, 2020)
To counteract the deadly pathogens i.e., Y. pestis, Y. enetrocolitica and Y. pseudotuberculosis, here, we prepared a recombinant DNA construct lcrV-hsp70 encoding the bivalent fusion protein LcrV-HSP70. The lcrV gene of Y. pestis and hsp70 domain II DNA fragment of M. tuberculosis were amplified by PCR. The lcrV amplicon was first ligated in the pET vector using NcoI and BamHI restriction sites. Just downstream to the lcrV gene, the hsp70 domain II was ligated using BamHI and Hind III restriction sites. The in-frame and the orientation of cloned lcrV-hsp70 were checked by restriction analysis and nucleotide sequencing. The recombinant bivalent fusion protein LcrV-HSP70 was expressed in E. coli and purified by affinity chromatography. The vaccine potential of LcrV-HSP70 fusion protein was evaluated in formulation with alum. BALB/c mice were vaccinated, and the humoral and cellular immune responses were studied. The fusion protein LcrV-HSP70 induced strong and significant humoral immune response in comparison to control animals. We also observed a significant difference in the expression levels of IFN-γ and TNF-α in LcrV–HSP70 immunized mice in comparison to control, HSP70 and LcrV groups. To test the protective efficacy of LcrV–HSP70 fusion protein against plague and Yersiniosis, the vaccinated mice were challenged with Y. pestis, Y. enterocolitica, and Y. pseudotuberculosis separately. The bivalent fusion protein LcrV–HSP70 imparted 100% protection against the plague. In the case of Yersiniosis, on day 2 post challenge, there was a significant reduction in the number of CFU of Y. enterocolitica and Y. pseudotuberculosis in the blood (CFU/ml) and the spleen (CFU/g) of vaccinated animals in comparison to LcrV, HSP70, and control group animals.